A Retrospective Study of Erectile Function and Use of Erectile Aids in Prostate Cancer Patients After Radical Prostatectomy in Denmark. Issue 3 (1st August 2017) - Haahr, Martha Kirstine; Azawi, Nessn H.; Andersen, Line Grønbaek; Carlson, Steen; Lund, Lars
Abstract: Introduction: Radical prostatectomy (RP) offers a good long-term cancer control for clinically localized prostate cancer. However, complications such as erectile dysfunction and substantial decreases quality of life of the afflicted men and their sexual partners. Identification of pre-, per-, and postoperative factors that correlate with poor postoperative erectile status must be considered an important step to improving penile rehabilitation. Aim: To describe postoperative erectile function after RP in a Danish cohort. Methods: The medical records of 1, 127 patients undergoing RP from March 2003 through September 2014 were reviewed retrospectively with a 12-month follow-up after surgery. In all, 704 patients fulfilling the inclusion criteria were included in the final analysis. Recovery was defined as self-reported erection sufficient for intercourse (ESI) with or without usage of erectile aids. Main Outcome Measures: Subjective reporting of erectile function and usage erectile aids 12 months after RP. Results: ESI with or without erectile aids was reported by 226 men (32.1%), among whom 109 (48.2%) required erectile aids. Erectile dysfunction (ED) was reported by 478 men (67.9%) and by 121 (25.3%) despite use of erectile aids. Of men with ED, 155 (22%) stated not being interested in penile rehabilitation, 26 (3.7%) stated not having resumed their sex life 12 months after RP, and 241 (34.2%) had ED and were unsatisfied with the condition. We found that 134 of 445 men (30.1%) who underwent non–nerve-sparing RP had ESI 12 months after RP. Age older than 60.5 years, a high body mass index, comorbidity, and a high American Society of Anesthesiologists score were negative predictors of erectile function 12 months after RP. Conclusion: Twelve months after RP, 32.1% of men had ESI; half these men required the use of erectile aids. Age older than 60.5 years, a high body mass index, comorbidity, and a high American Society of Anesthesiologists score were negative predictors for ED 12 months after RP. Haahr MK, Azawi NH, Andersen LG, et al. A Retrospective Study of Erectile Function and Use of Erectile Aids in Prostate Cancer Patients After Radical Prostatectomy in Denmark. Sex Med 2017;5:e156–e162 .